2010
DOI: 10.1038/ijo.2010.86
|View full text |Cite
|
Sign up to set email alerts
|

Cord lining progenitor cells: potential in vitro adipogenesis model

Abstract: Objective: To investigate the effect of glucose and insulin concentrations on differentiation of umbilical cord lining progenitor cells to adipocyte-like cells (ALCs). Methods: Cord lining mesenchymal cells (CLMCs) were isolated from the explant of human umbilical cord amniotic membrane. CLMCs were subjected to differentiation under various culture conditions for 20 days. Lipid droplets were confirmed with Oil Red O staining. Gene expressions of adipsin and peroxisome proliferator-activated receptor gamma (PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…In line with our results, a few studies on human cell models confirmed decreased APN expression after exposure to HG during the differentiation stage [29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, a few studies on human cell models confirmed decreased APN expression after exposure to HG during the differentiation stage [29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…In our work, we observed that the rate of lipid accumulation during hASC differentiation on chip was also dependent on the feeding pulse frequency. This dependency was expected, because lipid accumulation rates decrease under hypoxia (37) and deprivation conditions (38), which can explain the lower lipid accumulation rate in hASCs at lower feed frequencies on chip (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…This has been confirmed in vivo by the absence of teratoma formation after the injection of CLMCs into the midthigh muscle mass of severe combined immunodeficient (SCID) mice (authors' unpublished data). CLMCs have been differentiated into osteoblasts, chondro cytes, neurons (including dopamine-secreting neurons), fibroblasts, and adipocytes (5), demonstrating their multipotent nature.…”
Section: Cord Lining Mesenchymal Cells (Clmcs)mentioning
confidence: 99%